Pentecostal hermeneutics : a reader - Martin, Lee Roy (Brill, 2013)
In Pentecostal Hermeneutics: A Reader Lee Roy Martin presents fourteen significant publications on Pentecostal biblical interpretation, a new introduction to Pentecostal hermeneutics, and an extensive bibliography. These essays trace the development of Pentecostal hermeneutics as an academic discipline.